Pengaruh Employer Branding, Nilai Sosial Organisasi, dan Career Development Terhadap Retensi Talenta Muda dengan Kepuasan Kerja Sebagai Variabel Mediasi di Yayasan Yuk Peduli - Nurwan Rifai Herdiana; Irfan Nabhani; Minto Minto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Research on young talent retention has become an important issue in human resource management, particularly in non-profit organizations that often face limitations in providing financial compensation. Therefore, organizations need to understand non-financial factors that influence job satisfaction and employees’ decisions to remain in the organization. This study aims to analyze the influence of employer branding, organizational social values, and career development on young talent retention with job satisfaction as a mediating variable at Yayasan Yuk Peduli. The study employed a quantitative approach using a survey method involving 100 respondents who represent young talents in the organization. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The results indicate that employer branding, organizational social values, and career development have a positive and significant effect on job satisfaction. However, these variables do not have a significant direct effect on talent retention, and job satisfaction does not mediate the relationship between the independent variables and retention. These findings suggest that organizational factors play a greater role in shaping job satisfaction than in encouraging long-term retention. Therefore, non-profit organizations need to develop more comprehensive talent management strategies to strengthen employee loyalty and commitment.